Dynamical Coupling Atomistic and Continuum Simulations (Communications in Computational Physics, 2011)
We propose a new multiscale method that couples molecular dynamics simulations(MD) at the atomic scale and finite element simulations (FE) at the continuumregime. By constructing the mass matrix and stiffness matrix dependent on coarseningof grids, we find a general form of the equations of motion for the atomic andcontinuum regions. In order to improve the simulation at finite temperatures, we proposea low-pass phonon filter near the interface between the atomic and continuumregions, which is transparent for low frequency phonons, but dampens the high frequencyphonons.